The Influence of Economic Inequality, Political Polarization, and Media Misinformation on Civic Engagement: The Mediating Role of Social Trust - Laraib Khan; Alina Raza; Arooj Fatima, (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Civic engagement serves as the foundation of a thriving democracy, yet it is increasingly threatened by economic inequality, political polarization, and media misinformation. This study examines how these sociopolitical forces shape citizens' willingness to participate in civic activities, with a particular focus on the mediating role of social trust. Grounded in Social Capital Theory and Political Behavior Models, this research aims to provide an empirical understanding of how structural disparities and information distortions influence democratic participation in urban and rural communities of Pakistan. A cross-sectional survey design was employed, collecting data from 600 individuals across diverse socioeconomic backgrounds. This study makes a substantial contribution to political sociology, democratic studies, and social policy, highlighting the urgent need for policy reforms that promote economic inclusion, reduce political divisions, and combat misinformation. The findings carry critical implications for policymakers, civil society organizations, and media regulators, urging them to implement strategies that rebuild public trust, enhance civic participation, and foster a more inclusive democratic environment. By addressing these barriers, governments and social institutions can strengthen civic engagement, reinforce democratic resilience, and cultivate a more politically empowered society